Day-ahead and intra-day two-stage low-carbon economic scheduling method considering multi-form energy-intensive load - Yuan, Zhijun; Wang, Yibo; Xu, Yueyang; Liu, Chuang; Ge, Weichun; Cai, Guowei; Zhou, Jianing; Sun, Ao; Liu, Xin; Li, Baihe (Frontiers in Energy Research, 2023)
To solve the problem of the large gap in the regulation resources of the power system due to the large number of wind power connected to the grid and to help achieve the strategic energy goal of “carbon neutrality and carbon peaking,” the demand-side adjustable energy-intensive load is taken as the research object in this paper, and a two-stage low-carbon economic scheduling method of the wind power system with multi-form energy-intensive load (MEL) is proposed. First, the operating characteristics of the system with MEL are analyzed. At the same time, a refined mathematical model that conforms to the actual operation characteristics is established. Then, the complementary low-carbon characteristics of the source-charge side and the difference in the response characteristics of the demand-side MEL are considered. Meanwhile, combining with the energy storage system, a day-ahead and intra-day two-stage low-carbon economic scheduling model of the wind power system with MEL is constructed. Finally, an example of the improved IEEE-39 bus system is analyzed to verify the effectiveness of the proposed scheduling method in the low-carbon economic scheduling of wind power systems and to provide a reference for power grid scheduling.